The Effect of the Student Facilitator and Explaining (SFE) Type Learning Model on Students' Critical Thinking Skills Related to Heat Material - Efriyani; Emi Sulistri; Haris Rosdianto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article discusses research on the effect of the SFE learning model on improving students' critical thinking skills related to heat material. the researcher used a quasi-experimental method with a non-equivalent control group design. The sample of this research was class XI IPA 3 with 28 students as the control class and class XI IPA 4 with 28 students as the experimental class. in one Singkawang State High School with a sampling technique in the form of purposive sampling technique. After analysis, it is known that the data obtained is homogeneous and normally distributed. So the researchers used a parametric statistical test, namely the t-test. From the calculation results, the data obtained is greater than 6.25 > 1.69, then Ha is accepted at the 5% significance threshold and H0 is rejected, which means that the SFE learning model has an impact on students' critical thinking on heat material